2014
DOI: 10.1161/hypertensionaha.114.03352
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ERK1/2 Phosphorylation: A New Strategy to Stimulate Elastogenesis in the Aorta

Abstract: Abstract-Haploinsufficiency of elastin leads, in more than half of patients with Williams-Beuren syndrome, to development of supravalvular aortic stenosis and hypertension. Determining mechanisms implicated in elastin synthesis would be of interest to find new elastogenic molecules to treat such a pathology. Here, we analyzed the signaling pathway linking intracellular calcium concentration to elastin regulation to find new molecules able to increase elastin synthesis. Their elastogenic ability was then invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…Further analyses revealed that activation of ERK mediates EGF inhibition of elastogenesis. Inhibition of ERK blocked EGF effects on elastogenesis (Liu et al, 2003;DiCamillo et al, 2002;DiCamillo et al, 2006), whereas activation of ERK inhibited elastogenesis (Lannoy et al, 2014). Consistent with these reports, we found that levels of p-ERK were indeed increased in the Pdgfra Gli1 lungs (Fig.…”
Section: Pdgfra Controls a Second Tier Of Signaling Networksupporting
confidence: 90%
“…Further analyses revealed that activation of ERK mediates EGF inhibition of elastogenesis. Inhibition of ERK blocked EGF effects on elastogenesis (Liu et al, 2003;DiCamillo et al, 2002;DiCamillo et al, 2006), whereas activation of ERK inhibited elastogenesis (Lannoy et al, 2014). Consistent with these reports, we found that levels of p-ERK were indeed increased in the Pdgfra Gli1 lungs (Fig.…”
Section: Pdgfra Controls a Second Tier Of Signaling Networksupporting
confidence: 90%
“…Hence, the blackberrydill combination identified here could potentially be used for wrinkle-reducing treatment to provide anti-ageing skin benefits. Although other studies have shown elastogenesis stimulation through single ingredients [11,18,[43][44][45], this is the first study to use a comprehensive approach to upregulate elastogenesis stimulation in adults by combining two extracts that increase skin's functional elastic fibre production as well as prevent their degradation. Taken together, our studies identified a combination of two complementary natural extracts with elastogenic, skinfirming and sagging-reducing benefits for ageing and photodamaged skin.…”
Section: Discussionmentioning
confidence: 99%
“…An MMP activation inhibitor PD166739 markedly blunts elastin fiber degradation 3 . In addition, MMP activation triggers phosphorylation of ERK-1/-2, which retards tropoelastin production in VSMCs in vitro and elastogenesis in the rat aorta in vivo 16, 24 . These findings suggest that proliferation in which p-ERK-1/-2 is involved is coupled to the elastogenesis in VSMCs.…”
Section: Role Of Mmp Activation In Arterial Remodelingmentioning
confidence: 99%